A concise dictionary of comics - Pedri, Nancy (University Press of Mississippi, 2022)
"Written in straightforward, jargon-free language, A Concise Dictionary of Comics guides students, researchers, readers, and educators of all ages and at all levels of comics expertise. It provides them with a dictionary that doubles as a compendium of comics scholarship. A Concise Dictionary of Comics provides clear and informative definitions for each term. It includes twenty-five witty illustrations, and pairs most defined terms with references to books, articles, book chapters, and other relevant critical sources. All references are dated and listed in an extensive, up-to-date bibliography of comics scholarship. Each term is also categorized according to type in an index of thematic groupings. This organization serves as a pedagogical aid for teachers and students learning about a specific facet of comics studies and as a research tool for scholars who are unfamiliar with a particular term but know what category it falls into. These features make A Concise Dictionary of Comics especially useful for critics, students, teachers, and researchers, and a vital reference to anyone else who wants to learn more about comics"--